2006
DOI: 10.1002/elan.200603700
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Immunoanalysis for Carcinoembryonic Antigen Based on Multilayer Architectures of Gold Nanoparticles and Polycation Biomimetic Interface on Glassy Carbon Electrode

Abstract: This paper describes a layer-by-layer (LBL) self-assembly process of chitosan (CTS) and gold nanoparticles (Au) on the pretreated negatively charged glassy carbon (GC) electrode to fabricate electrochemistry immunosensor with a nontoxic biomimetic interface, which provided an environment similar to a native system and allowed more freedom in orientation for immobilization of carcinoembryonic antibody (anti-CEA) to monitor carcinoembryonic antigen (CEA). UV-vis spectroscope, atomic force microscopy (AFM), and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…7 In the form of low molecular weight or oligomers, it also has a perspective for protection against DNA oxidative damage. 8 In the field of sensors, CHIT was already widely used, for instance amperometric laccase sensing at a glassy carbon electrode, 9 amperometric glucose sensing at a Pt electrode, 10 imunosensing for carcinoembryonic antigen at a glassy carbon electrode with CHIT/Au nanoparticles, 11 hydrogen peroxide sensing at a glassy carbon 12 for the detection of DNA hybridization using CNT/nano zirconium dioxide/CHIT-modified electrodes 13 and for the determination of a colorectal cancer target DNA sequence using a CeO2/CHIT composite matrix. 14 CNTs precipitate in water and in acidic aqueous solutions due to their aggregation caused by hydrophobic interactions and van der Walls forces between the tubes.…”
Section: Introductionmentioning
confidence: 99%
“…7 In the form of low molecular weight or oligomers, it also has a perspective for protection against DNA oxidative damage. 8 In the field of sensors, CHIT was already widely used, for instance amperometric laccase sensing at a glassy carbon electrode, 9 amperometric glucose sensing at a Pt electrode, 10 imunosensing for carcinoembryonic antigen at a glassy carbon electrode with CHIT/Au nanoparticles, 11 hydrogen peroxide sensing at a glassy carbon 12 for the detection of DNA hybridization using CNT/nano zirconium dioxide/CHIT-modified electrodes 13 and for the determination of a colorectal cancer target DNA sequence using a CeO2/CHIT composite matrix. 14 CNTs precipitate in water and in acidic aqueous solutions due to their aggregation caused by hydrophobic interactions and van der Walls forces between the tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Differential pulse voltammetry has also shown its usefulness in the development of direct immunosensors for PSA [32], CEA [33][34][35], and CA 125 [36] determination, using CNTs [32], AuNPs [33,34,36], and magnetic NPs [34,35]. Thus, in a flow injection assay for CEA determination in serum, the surface of a pretreated negatively charged glassy carbon electrode was modified with cationic chitosan and anionic AuNPs, previously to the immobilization of the antibodies [33].…”
Section: Direct Assaysmentioning
confidence: 99%
“…Thus, in a flow injection assay for CEA determination in serum, the surface of a pretreated negatively charged glassy carbon electrode was modified with cationic chitosan and anionic AuNPs, previously to the immobilization of the antibodies [33]. CEA has been also determined in serum using magnetic Fe 2 O 3 -core/Au-shell composite NPs as affinity support for antibody adsorption [34].…”
Section: Direct Assaysmentioning
confidence: 99%
“…Because AuNPs have a large area‐to‐volume ratio that facilitates surface absorption of protein molecules, they are ideal candidates for antibody immobilization. For instance, Yuan et al fabricated a CEA immunosensor via layer‐by‐layer assembly of cationic chitosan and anionic AuNPs on glassy carbon electrodes . The CEA antibody was subsequently immobilized on the electrodes.…”
Section: Nanodevices For In Vitro Applicationsmentioning
confidence: 99%
“…For instance, Yuan et al fabricated a CEA immunosensor via layer-by-layer assembly of cationic chitosan and anionic AuNPs on glassy carbon electrodes. 95 The CEA antibody was subsequently immobilized on the electrodes. In their follow-up study, they reported another CEA immunosensor based on AuNPs/Nano-CaCO 3 /Prussian-blue modified glassy carbon electrodes with a detection limit of 0.1 ng/ml.…”
Section: Nanodevices For In Vitro Applicationsmentioning
confidence: 99%